A COMPARATIVE STUDY OF DISTRICT INDUSTRIES CENTRE LISTED ENTREPRENEURS OF ASSAM WITH SPECIAL REFERENCE TO JORHAT DISTRICT - Das, Naba (International Journal of Engineering Technologies and Management Research, 2018)
This study aims to examine the trend of assorted DIC registered business enterprise in Jorhat district of Assam. Data of six financial year i.e. 2010-11 to 2015-16 are taken into consideration to measures the various aspects which are related to entrepreneurial growth and employment generation. By comprising four objectives, this study attempts to focus on various areas such as engagement of male and female entrepreneurs in manufacturing and service sector, share of various of agro and non-agro based enterprises, employment generation scenario and impact of investment in plant and machinery in annual turnover. In the study it was found that in the initial three years share of male entrepreneurs was more and from the financial year 2014-15 to 2015-16, share of female entrepreneurs increased drastically. The weightage of non-agro based business is much higher than agro-based business and ratio of annual turnover to investment in plant and machinery marginal except in the year 2012-13 which was 17:1.